Natural Flavonoids from Licorice as Potent Inhibitors of β-Glucuronidase Elucidated Through Computational Studies - Jingli Liu; Yingying Xue; Hao Yan; Jing Zhou; Xu Long; Yuping Tang (Molecules)
Gut bacterial β-glucuronidase is an important molecular target in several therapeutic applications. β-glucuronidase inhibitors can effectively alleviate gastrointestinal toxicity caused by certain drugs. Licorice, a traditional Chinese medicine, harmonizes various herbs and mitigates the toxicity of hundreds of herbs. In this study, a comprehensive computational strategy was employed to evaluate four licorice flavonoids (liquiritigenin, isoliquiritigenin, liquiritin, and isoliquiritin) as potential Escherichia coli β-glucuronidase (EcGUS) inhibitors. Density functional theory was used to determine their geometries, thermal parameters, dipole moments, polarizabilities, and molecular electrostatic potentials. The inhibitory mechanisms of these four flavonoids on EcGUS were investigated using molecular docking, molecular dynamics simulations, and free energy calculations. The results show that all four flavonoids stably bind to EcGUS. Moreover, all molecules, except liquiritigenin, are potent and selective inhibitors of EcGUS. Further calculations suggest that isoliquiritin exhibits the strongest binding affinity for EcGUS among the four licorice flavonoids. Thus, isoliquiritin is a promising candidate for the development of EcGUS inhibitors. These findings will aid in designing and developing novel flavonoid-based inhibitors of EcGUS to alleviate gastrointestinal toxicity caused by drugs.